Pengaruh Interface Characteristics dan System Quality terhadap Behavioural Intention to Use Application - Areta Amadea Dewandaru; Magnaz Lestira Oktaroza (UNISBA Press, 2022)
Abstract. This research is based on the phenomenon that occurs, where there are still many users of food delivery service applications who find it difficult to operate the application because of the complicated appearance, thus making users not intend to use food delivery service applications. This study aims to examine the interface characteristics and system quality of the behavioral intention to use the application. This research was conducted in Tamansari Village, Bandung City using descriptive and verification research methods and quantitative approaches. This study uses primary data collected through questionnaires and the determination of respondents is based on convenience sampling. According to the established criteria, Questionnaires were distributed to users of the food delivery service application in Tamansari Village, Bandung City. The results showed that the interface characteristics, system quality, and behavioral intention to use the application were good. Interface characteristics have an effect but not significantly on behavioral intention to use application by 3.6%, and system quality has a significant effect on behavioral intention to use application by 45.6%. Abstrak. Penelitian ini didasarkan pada fenomena yang terjadi, dimana masih banyak pengguna aplikasi layanan pesan antar makanan yang merasa kesulitan untuk mengoperasikan aplikasi tersebut karena tampilan yang rumit, sehingga membuat para pengguna tidak berniat untuk menggunakan aplikasi layanan pesan antar makanan. Penelitian ini bertujuan untuk menguji interface characteristics dan system quality terhadap behavioural intention to use application. Penelitian ini dilakukan di Kelurahan Tamansari Kota Bandung dengan menggunakan metode penelitian deskriptif dan verifikatif dan pendekatan kuantitatif. Penelitian ini menggunakan data primer yang dikumpulkan melalui kuesioner dan penentuan responden didasarkan pada convenience sampling. Sesuai dengan kriteria yang ditetapkan, kuesioner dibagikan kepada pengguna aplikasi layanan pesan antar makanan di Kelurahan Tamansari Kota Bandung. Hasil penelitian menunjukkan bahwa interface characteristics, system quality, dan behavioural intention to use application sudah baik. Interface characteristics berpengaruh tetapi tidak signifikan terhadap behavioural intention to use application sebesar 3.6%, dan system quality berpengaruh signifikan terhadap behavioural intention to use application sebesar 45,6%.